+0  
 
0
96
2
avatar

f'(-4) if f(x) = x^2-x

So I'm calculating 

f´(-4) = lim(h goes against 0) (f(-4+h)-f(-4))/h

f´(-4) = lim(h goes against 0) ((-4+h)^2+4+4^2-4)/h

f´(-4) = lim(h goes against 0)(4^2-4^2-8h+h^2)/h

f´(-4) = lim(h goes against 0)h(-8+h)/h

f´(-4) = lim(h goes against 0) -8+h

f´(-4) = -8

 

I know the answer should be -9 since the diverate of f(x) = x^2-x should be 2x - 1 (-4*2-1) but I can't make it work :(

Guest May 29, 2017
Sort: 

2+0 Answers

 #1
avatar+76929 
+1

By definition, we have

 

[ (x + h)^2  - (x + h)  -  ( x^2 - x )  ]  /  h   =

 

[ x^2 + 2xh + h^2 - x - h  -  x^2  + x ]  /  h  =

 

[ 2xh  + h^2 -  h]  / h   =

 

[ (h)( 2x  + h  -  1 )]  / h   =     divide by h on top/bottom

 

[ 2x  + h  -  1 ]        let  h →  0     and we have

 

[ 2x  -  1 ]  =   f ' (x)

 

 

So

 

f '(-4)   =    2(-4)  -  1    =  - 8  -  1    =    - 9

 

 

 

cool cool cool

CPhill  May 29, 2017
 #2
avatar
0

Riight, forgot that you add (x+h) into all x terms in the function, thank you!

Guest May 29, 2017

8 Online Users

avatar
We use cookies to personalise content and ads, to provide social media features and to analyse our traffic. We also share information about your use of our site with our social media, advertising and analytics partners.  See details